Increasing Oleoresin (Pinus merkusii) Productivity with Physical Treatment Modification and Time of Tapping in Riil Method - Wilna Fikriyah Hasibuan; Ridwanti batubara; Muhdi Muhdi (Peronema Forestry Science Journal, 2014)
Pinus merkusii is one of endemic in North Sumatera, especially in the north. Pine has a very impotant role, whereas beside as a pioneer plant, pine also produces resin which if we process it more, it will has higher economic value. The purpose of this research were to knowing the influence between time of tapping with physical treatment modification in riil method of oleoresin productivity. In this research, the physical treatment used were by hitting (without hitting, 10,20, and 30 times hitting). The result of this research showed that 10 times hitting were different than 20 and 30 times hitting, while 20 and 30 times hitting were not different. The highest amount of oleoresin productivity were from 10 times hitting (1,428 kg/tree/year) which showed that physical treatment of 10 times hitting were better than 20 and 30 times hitting. The times of tapping 3 days at once was very different with the times of tapping 5 and 7 days at once, while the times of tapping 5 and 7 days at once were not different. The times of tapping 3 days at once has a significant influence and it was the best times of tapping for increasing oleoresin productivity.Key words : Pinus merkusii , resin, riil method, times of tapping